2022
DOI: 10.1155/2022/9943247
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Adolescents and Young Adults Less Than 40 Years of Age in Nigeria: A Retrospective Analysis

Abstract: Background. Breast cancer among adolescents and young adult (AYA) females aged 15-39 years is associated with different patterns of aggressiveness, as well as psychosocial and economic issues. At present, the burden of breast cancer among this age group is unknown in Nigeria. There is a need to determine the proportion of AYA with breast cancer in Nigeria. This will inform the development of breast cancer care programs appropriate for this age group. Objective. The objective of this study was to highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…This study showed that breast cancer occurs primarily in the young and middle-aged groups in this environment. This is similar to the findings of other studies in Nigeria which showed that breast cancer occurs at a younger age compared to Caucasians [4,[24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that breast cancer occurs primarily in the young and middle-aged groups in this environment. This is similar to the findings of other studies in Nigeria which showed that breast cancer occurs at a younger age compared to Caucasians [4,[24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…A recent retrospective study in Nigeria among adolescents and young adult females aged 15 to 39 years showed that breast cancer was the most common cancer, accounting for 50% of all cancers. The adolescents and young adult females breast cancer patients constituted 51% of all breast cancer cases 5,6 . Similar findings are made in Togo, where breast cancer ranks first in female cancers, accounting for 21.2%, and strucks 38.3% of women under the age of 40 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There are considerable epidemiological and biological variations between blacks and whites with breast cancer, which has far-reaching consequences for the establishment of an efficient cancer screening program in Nigeria. Ntekim et al [12], did a study with the goal of describing the clinicopathologic aspects of breast cancer identified at their hospital and discussing the implications for cancer screening. They conclude that there are major epidemiological and biological differences between breast cancer in Lagos and in western populations that must be addressed in order to build an effective breast cancer screening program that is specifically adapted to the Nigerian population.…”
Section: Introductionmentioning
confidence: 99%